TO THE SUBJECT OF DEVELOPMENT OF POWER SUPPLY PROCESS FOR INDUSTRIAL HEAT TECHNOLOGIES AND HEAT SUPPLY SYSTEMS IN BELARUS - B. M. Khrоustalev; V. N. Romaniuk; V. A. Sednin; A. A. Bobich; D. B. Muslina; T. V. Bubyr (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
Considers the current key energy problem – the rational and efficient use of energy resources, and the possibility of its solution, based on the concept of intensive energy conservation. As a result, the way of primary energy consumption reduction in Belarus is provided. The initial situation in the frame of program of further improvement of energy consumption until 2030 is estimated. It is shown, that for Belarus the first place in energy saving measures takes the efficiency improvement of natural gas consumption, what allows reducing the investment and saving energy resources.The possibility of usage of waste energy flows of medium-and low-temperature from industrial and municipal enterprises are discussed. To realize the described possibilities, some changes of heat supply system of enterprises and plants are required. Changes in heat supply system of the industrial enterprises, related with usage of low-temperature waste energy flows in a thermal energy generation process for heating, require the installation of additional equipment in existing heat energy supply system, such as absorption heat pumps, which are easily joint and successfully work at boiler Houses as well as at CHP. The numerous examples of fuel consumption reduction via heat industrial waste and sewage usage are shown in this article. It must be emphasized, that such an expansion of energy-saving framework not only reduce the primary energy consumption by heat generating sources, but also significantly improves the conditions of the Belarusian electrical grid operation under the conditions of nuclear power plant commissioning. The existing technical framework, that ensured the proposed changes, is also taking into account.